Model experiments on growth modes and interface electronics of CuInS2: Ultrathin epitaxial films on GaAs(100) substrates. Issue 9 (19th July 2014) - Calvet, Wolfram; Lewerenz, Hans‐Joachim; Pettenkofer, Christian
<x xml:space="preserve">Abstract</x> The heterojunction formation between GaAs(100) and CuInS2 is investigated using ultraviolet photoelectron spectroscopy (UPS), X‐ray photoelectron spectroscopy (XPS), and low energy electron diffraction (LEED). Thin layers of CuInS2 films were deposited in a step‐by‐step process on wet chemically pre‐treated GaAs(100) surfaces by molecular beam epitaxy (MBE) with a total upper thickness limit of the films of 60 nm. The film growth starts from a sulfur‐rich GaAs(100) surface. XPS core level analysis of the substrate and film reveals initially a transitory growth regime with the formation of a Ga containing chalcopyrite phase. With increasing film thickness, a change in stoichiometry from Cu‐poor to Cu‐rich composition is observed. The evaluation of the LEED data shows the occurrence of a recrystallization process where the film orientation follows that of the substrate with the epitaxial relation GaAs{100}||CuInS2{001}. On the completed junction with a CuInS2 film thickness of 60 nm, the band discontinuities of the GaAs(100)/CuInS2 structure measured with XPS and UPS were determined as ΔEV = 0.1 ± 0.1 eV and ΔEC = 0.0 ± 0.1 eV, thus showing a type II band alignment.